An amplified promoter system for targeted expression of calcium indicator proteins in the cerebellar cortex - Kuhn, Bernd; Ozden, Ilker; Lampi, Yulia; Hasan, Mazahir T.; Wang, Samuel S. (Frontiers in Neural Circuits, 2012)
Recording of identified neuronal network activity using genetically encoded calcium indicators (GECIs) requires labeling that is cell type-specific and bright enough for the detection of functional signals. However, specificity and strong expression are often not achievable using the same promoter. Here we present a combinatorial approach for targeted expression and single-cell-level quantification in which a weak promoter is used to drive trans-amplification under a strong general promoter. We demonstrated this approach using recombinant adeno-associated viruses (rAAVs) to deliver the sequence of the GECI D3cpv in the mouse cerebellar cortex. Direct expression under the human synapsin promoter (hSYN) led to high levels of expression (50-100 µM) in five interneuron types of the cerebellar cortex but not in Purkinje cells (PCs) (≤10 μM), yielding sufficient contrast to allow functional signals to be recorded from somata and processes in awake animals using two-photon microscopy. When the hSYN promoter was used to drive expression of the tetracycline transactivator (tTA), a second rAAV containing the bidirectional TET promoter (Ptetbi) could drive strong D3cpv expression in PCs (10-300 µM), enough to allow reliable complex spike detection in the dendritic arbor. An amplified approach should be of use in monitoring neural processing in selected cell types and boosting expression of optogenetic probes. Additionally, we overcome cell toxicity associated with rAAV injection and/or local GECI overexpression by combining the virus injection with systemic pre-injection of hyperosmotic D-mannitol, and by this double the time window for functional imaging.